Water for all: Making SDG 6 a reality - Ringler, Claudia; Mehta, Lyla; Schreiner, Barbara; Oweis, Theib; Varghese, Shiney (DLG-Verlag GmbH, 2020)
Water for all is an important concept embedded in Sustainable Development Goal 6 on Water and Sanitation. However, implementation does not currently target differential access for women and marginalised people. Our authors show what actions are needed to resolve growing tensions around water scarcity and degradation, thus meeting the needs of the poor and vulnerable.